The Prisonized Old Head: Intergenerational Socialization and the Fusion of Ghetto and Prison Culture. (December 2017) - Stuart, Forrest; Miller, Reuben Jonathan
Over the last four decades, the United States' criminal justice system has undergone a historic expansion, which has disproportionately impacted poor urban neighborhoods. The meteoric rise in the percentage of the urban poor either on their way to, in, or recently released from jail or prison has led a number of scholars to theorize a "fusion of ghetto and prison culture" (Wacquant 2001). The exact sources and contours of this fusion, however, remain unspecified. How, concretely, are the cultural contexts of prisons transmitted to poor urban neighborhoods? This article proposes that intergenerational socialization is a key mechanism in this process. We contend that the dramatic expansion of the criminal justice system over the last four decades has given rise to an unexpected and peculiar form of socialization, provided by a new social actor—what we term the "prisonized old head." We define the prisonized old head as an individual who exhibits three particular characteristics. They are (1) older individuals with extensive experiences in, and wisdom about, the criminal justice system; who (2) informally socialize neighborhood residents to embrace the cultural schemas and routines learned inside penal spaces; to (3) navigate the daily exigencies routinely faced in the neighborhood context. Stated simply, prisonized old heads leverage ways of life developed "on the inside" as strategies for living life "on the outside." We articulate the emergence, mechanisms, and implications of this form of socialization drawing on fieldwork data in Los Angeless' Skid Row neighborhood—one of the premier reentry communities in the United States. We show that although this socialization may contribute to desistance and self-transformation, it can simultaneously constrain upward mobility and limit reintegration.